(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Content of article refers to wrap of product and feature utilitarian, esthetic and economic. So, all these features, which effect decisions of purchasers to important man-ner in process of shopping, as well as they form understood quality of use of product widely. It perform with reference to creamery products analysis of meaning of feature of above-mentioned wrap, wrap is particularly important for which Majority of creamery product presents products integrated, or such, which can not be sold without wrap. It take attempt of verifying of existence of statistic dependence on base of assembled empirical material among described features of wraps also but kind of creamery prod-uct, it perform which discrimination according to criterion of consistency liquid and illiquid.